2007
DOI: 10.1002/hyp.6857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hillslope topography on hydrological responses in a weathered granite mountain, Japan: comparison of the runoff response between the valley‐head and the side slope

Abstract: Abstract:To evaluate the effects of hillslope topography on storm runoff in a weathered granite mountain, discharge rate, soil pore water pressures, and water chemistry were observed on two types of hillslope: a valley-head (a concave hillslope) and a side slope (a planar hillslope). Hydrological responses on the valley-head and side slope reflected their respective topographic characteristics and varied with the rainfall magnitude. During small rainfall events (<35 mm), runoff from the side slope occurred rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 35 publications
(44 reference statements)
5
39
0
2
Order By: Relevance
“…Advances in using digital elevation models (DEM) to generate simple topography-based run-off predictions have highlighted the need for detailed field data to characterize how surface topography specifically influences soil moisture, shallow water tables, and run-off Western et al, 1999;Fujimoto et al, 2008). The use of a similarity approach to hydrologic modelling likewise often relies on a DEM to subdivide a watershed into elementary units defined by topography, climate, and soils as a means of characterizing physical processes (Aryal et al, 2002;Harman and Sivapalan, 2009).…”
Section: Topographic Controls On Shallow Groundwater Dynamics 2223mentioning
confidence: 99%
“…Advances in using digital elevation models (DEM) to generate simple topography-based run-off predictions have highlighted the need for detailed field data to characterize how surface topography specifically influences soil moisture, shallow water tables, and run-off Western et al, 1999;Fujimoto et al, 2008). The use of a similarity approach to hydrologic modelling likewise often relies on a DEM to subdivide a watershed into elementary units defined by topography, climate, and soils as a means of characterizing physical processes (Aryal et al, 2002;Harman and Sivapalan, 2009).…”
Section: Topographic Controls On Shallow Groundwater Dynamics 2223mentioning
confidence: 99%
“…Anderson and Burt (1978) showed that topography can control matric potential and downslope flow: at their field site, hillslope "hollows" had specific discharge an order of magnitude higher than hillslope spurs. Fujimoto et al (2008) found that topography interacts with storm size to control subsurface processes. For small storms, a concave hillslope stored more water than a planar slope and produced less runoff, whereas for larger storms, transient groundwater in the concave slope caused greater expansion of the saturated area than in the planar slope, and correspondingly greater runoff.…”
Section: Groundwater Variabilitymentioning
confidence: 99%
“…For instance, at the plot scale, Peters et al (1995) found that the runoff hydrographs of the shallow soil plots, compared with the deeper soil plots, closely resembled the shapes of the hyetographs, which were highly responsive to incoming rainfall, with synchronous peak intensities, and showed high recession rates after rainfall cessation. At the hillslope scale, Fujimoto et al (2008) noted that convergent hillslopes with deep soils had delayed runoff responses, whereas hillslopes with shallow soils produced highly peaked hydrographs.…”
Section: Introductionmentioning
confidence: 97%